Continuous insulin therapy versus multiple insulin injections in the management of type 1 diabetes: a longitutinal study - Maria Estela Bellini Ribeiro; Raphael Del Roio Liberatore Junior; Rodrigo Custodio; Carlos Eduardo Martinelli Junior (Revista Paulista de Pediatria, 2016)
Abstract Objective: To compare multiple doses of insulin and continuous insulin infusion therapy as treatment for type 1 diabetes mellitus. Methods: 40 patients with type 1 diabetes mellitus (21 female) with ages between 10 and 20 years (mean=14.2) and mean duration of diabetes of 7 years used multiple doses of insulin for at least 6 months and after that, continuous insulin infusion therapy for at least 6 months. Each one of the patients has used multiple doses of insulin and continuous insulin infusion therapy. For analysis of HbA1c, mean glycated hemoglobin levels (mHbA1c) were obtained during each treatment period (multiple doses of insulin and continuous insulin infusion therapy period). Results: Although mHbA1c levels were lower during continuous insulin infusion therapy the difference was not statistically significant. During multiple doses of insulin, 14.2% had mHbA1c values below 7.5% vs. 35.71% while on continuous insulin infusion therapy; demonstrating better glycemic control with the use of continuous insulin infusion therapy. During multiple doses of insulin, 15–40 patients have severe hypoglycemic events versus 5–40 continuous insulin infusion therapy. No episodes of ketoacidosis events were recorded. Conclusions: This is the first study with this design comparing multiple doses of insulin and continuous insulin infusion therapy in Brazil showing no significant difference in HbA1c; hypoglycemic events were less frequent during continuous insulin infusion therapy than during multiple doses of insulin and the percentage of patients who achieved a HbA1c less than 7.5% was greater during continuous insulin infusion therapy than multiple doses of insulin therapy.